PENGARUH PENGALAMAN BELANJA ONLINE, KEPUASAN PELANGGAN, DAN ADJUSTED EXPECTION TERHADAP NIAT MEMBELI KEMBALI MELALUI TRAVELOKA - Theresia, Ni Made Maya Devi Theresia; Wardana, I Made (E-Jurnal Manajemen; Vol 8 No 8 (2019)DO - 10.24843/EJMUNUD.2019.v08.i08.p07, 2019)
The purpose of this study was to determine the effect of online shopping experience, customer satisfaction, and adjusted expectations on the intention to repurchase. This research was conducted at Traveloka with a sample of 96 millennials domiciled in Badung Regency and Denpasar City, with a non probability sampling method specifically purposive sampling. The analytical tool used in this study is PLS (Partial Least Square). Based on the results of the analysis it was found that online shopping experience had a significant effect on customer satisfaction, the better the online shopping experience obtained by the customer, the more customer satisfaction will increase. Online shopping experience does not have a significant effect on adjusted expectations. Customer satisfaction has a significant effect on adjusted expectations, the higher the level of satisfaction then adjusted expectations will also increase. Customer satisfaction and adjusted expectations have a significant effect on repurchase intention. Keywords: experience, satisfaction, adjusted expectations, intention to epurchase.